Solidaritas Komunitas Suku Batak di Kelurahan Tuladenggi Kecamatan Dungingi Kota Gorontalo - Tamrin, Karmila Sri Sartika; Musa, Farid Th.; Harold, Rudy (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
This study aims to find out how Batak community solidarity forms in Gorontalo City. The existence of the Batak tribe is widespread in every area of Gorontalo City. Batak tribes come to Gorontalo with different purposes, one of which is to try their luck. Even though the Batak tribe lives separately, they always have moments to gather. The Batak ethnic community in Gorontalo is known as Saroha and Batagor Marsada. The method used in this research is qualitative with a descriptive approach. While data collection is done through observation, interviews, and documentation, The results of the study show that the form of solidarity possessed by two (two) communities from the Batak tribe who are overseas in Gorontalo City is a form of mechanical solidarity. This can be seen clearly with the members of the Saroha and Batagor Marsada communities, where they still carry out and preserve the values, norms, and traditional activities of their ancestral traditions. When they know that they are one ethnicity, then they lower their feelings of individuality and their sense of ego within themselves. They prefer to help each other among Batak ethnic groups, and what forms the solidarity of the two Batak ethnic communities in Tuladenggi Village, Dungingi District, and Gorontalo City is the spirit of regionalism and primordialism. Second, feelings of kinship and empathy Third, togetherness. Fourth, expand the network.